2021
DOI: 10.1038/s41598-021-02479-6
|View full text |Cite|
|
Sign up to set email alerts
|

A deep learning model for identifying diabetic retinopathy using optical coherence tomography angiography

Abstract: As the prevalence of diabetes increases, millions of people need to be screened for diabetic retinopathy (DR). Remarkable advances in technology have made it possible to use artificial intelligence to screen DR from retinal images with high accuracy and reliability, resulting in reducing human labor by processing large amounts of data in a shorter time. We developed a fully automated classification algorithm to diagnose DR and identify referable status using optical coherence tomography angiography (OCTA) imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 49 publications
2
25
0
1
Order By: Relevance
“…Similar results are also seen when using CNNs for DR severity grading; Ryu et al have recently developed a fully automated algorithm to classify DR stages with accuracy of 91-98%, sensitivity of 86-97%, and specificity of 94-99% (417,418). Application of these models can also establish biomarkers useful for diagnosis and treatment response; these could be structural (retinal layer measurement, hyperreflective foci) or vascular (areas of non-perfusion, vascular leakage, microaneurysm count, and neovascularization) (387).…”
Section: Artificial Intelligence and Diabetic Retinopathysupporting
confidence: 56%
“…Similar results are also seen when using CNNs for DR severity grading; Ryu et al have recently developed a fully automated algorithm to classify DR stages with accuracy of 91-98%, sensitivity of 86-97%, and specificity of 94-99% (417,418). Application of these models can also establish biomarkers useful for diagnosis and treatment response; these could be structural (retinal layer measurement, hyperreflective foci) or vascular (areas of non-perfusion, vascular leakage, microaneurysm count, and neovascularization) (387).…”
Section: Artificial Intelligence and Diabetic Retinopathysupporting
confidence: 56%
“…Different DL-models assess OCTA image quality assessment [ 142 ], object segmentation [ 143 ], and quantification [ 144 ], with high accuracies. Ryu et al developed a convolutional neural network (CNN) model classification algorithm with a sensitivity of 86–97%, a specificity of 94–99%, and an accuracy of 91–98% to diagnose DR through OCTA [ 145 ]. Le et al’s DL classifier differentiated among healthy, no DR, and DR eyes with 83.76% sensitivity, 90.82% specificity, and an 87.27% accuracy [ 146 ] and Heisler et al achieved an accuracy of between 90% and 92% [ 147 ].…”
Section: Resultsmentioning
confidence: 99%
“…DL system from Google AI Healthcare identified image features to grade fundus lesions derived from 128,175 retinal images (labeled by 54 ophthalmologists) and discovered that these image features could quickly identify DR and identify signs of DR. Ting et al reported a clinically acceptable diagnostic performance with an AUC of 93.6%, sensitivity of 90.5%, and specificity of 91.6%, in detecting DR using a development dataset acquired from Singapore integrated DR Program and several external datasets from six different countries (13). In another study, investigators from Aalto University trained a DL model based on Inception-v3 and found that DL could accurately separate DR and macular edema (35) (38).…”
Section: Diabetic Retinopathymentioning
confidence: 99%